Static and Dynamic Effects of Health Policy: Evidence from the Vaccine Industry - Finkelstein, A. (Quarterly Journal of Economics, 2004)
Public policies designed to increase utilization of existing technologies may also affect incentives to develop new technologies. This paper investigates this phenomenon by examining policies designed to increase usage of preexisting vaccines. I find that these policies were associated with a 2.5-fold increase in clinical trials for new vaccines. For several diseases, the induced innovation is socially wasteful, though small in magnitude. In one case, however, the "dynamic" social welfare benefits from induced innovation exceed the policies' "static" benefits from increasing vaccination with existing technology. These findings underscore the importance of including technological progress in economic analysis of public policy.